Timing of plutonism, deformation, and metamorphism in the Yellowknife Domain, Slave Province, Canada - Davis, W J; Bleeker, Wouter (Canadian Journal of Earth Sciences, 1999)
U-Pb zircon, titanite, and monazite ages for plutonic rocks are used to constrain the timing of post-2660 Ma deformational and metamorphic events in the Yellowknife Domain, southern Slave Province. Diorite and tonalite plutons of the Defeat Suite yield ages of 2628 ± 3 and 2624 ± 3 Ma, older than previous, less precise estimates for this suite of ca. 2618-2620 Ma. The Defeat Suite plutons crosscut and postdate upright F 1 folds in turbidites of the ca. 2680-2660 Ma Burwash Formation. D 1 deformation is therefore bracketed between 2660 and 2630 Ma. The D 1 event significantly predates deposition of polymict conglomerates of the Jackson Lake Formation. A second folding event (F 2 ), represented by northwest- to north-trending steeply plunging folds of bedding and D 1 structures, affected the area after intrusion of the Hidden Lake pluton at 2606 ± 2 Ma, and synchronously with intrusion of the 2596 ± 2 Ma Sparrow Lake pluton, a member of the two-mica granite Prosperous suite. The time of initiation and the duration of D 2 deformation are not well defined. It may have affected units as young as the 2586 ± 2 Ma Morose Granite. Metamorphic isograds are spatially related to Defeat, Prosperous, or even younger plutonic complexes, and therefore formed at different times over a 30 Ma period in different parts of the Yellowknife Domain. The ca. 2620-2630 Ma Defeat-type plutonism started in the Yellowknife Domain 10-15 Ma earlier than similar intrusive events in the central and northern Slave Province and highlights diachronous development of plutonism in the period from 2630 to 2610 Ma. In contrast, the ages of younger granites in the Yellowknife Domain (Prosperous, Morose) are within the range of intrusive ages documented for similar plutonic suites elsewhere in the Slave Province.